On Planar Harmonic Mappings And Minimal Surfaces - M. Ali, Rosihan; Lee, See Keong; V. Ravichandran, V. Ravichandran; K. G. Subramanian, K. G. Subramanian (Universiti Sains Malaysia, 2014)
The project seeks to study the geometric properties of planar harmonic mappings (and related mappings), and aims to apply the findings in the investigation of minimal surfaces.